SELF-CARE AGENCY PADA IBU NIFAS PRIMIGRAVIDA BERDASARKAN TEORI DOROTHEA E. OREM - Tri Sulistyarini (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: The puerperium period is a period that requires effective and optimal care. Passive postpartum mother to the environment that the mother is very dependent on others, expect everything needs by relying on others. Method: The purpose of this study was to study the description of Self Care Agency in Primigravida Puerperium Mother based on Dorothea E. Orem theory at Kediri Baptist Hospital.Design research in this research using descriptive method. The study population was Primigravida mother in Sarah Room of Baptist Hospital of Kediri. The sample was primigravida puerperium mother at sarah room of Baptist Hospital Kediri that meets the inclusion criteria of 25 respondents. Sampling used was consecutive sampling. The variable was Self Care Agency. Question used is DSCAI-90. Data processing used frequency distribution. Result: Based on the results of the study could be seen more than 50% of respondents included in the category of self-care agency was less 68% and 32% good. Discussion: The conclusion showed self care agency in primigravida puerperium mother based on Dorothea E. Orem theory that was less with characteristic of age 16-25 years, birth with sectio sesaria, live with parent / parent in-law, and include intermedial / early postpartum period